Critiquing Nationalism: A Study of Amitav Ghosh’s The Glass Palace: Exploring Nationalism and Identity in Amitav Ghosh's The Glass Palace (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The force of nationalism has become one of the most potent forces of our movements all over the world. Nationalism is born of the notion of a common heritage of people that stretches over a long past and shared ethnic and religious root. To seek to give this idea a fixed contour and to invest it with certain dimensions and defining features is tantamount to limiting the conditions under which the idea of the nation may constantly find meaningful existence and identity. Peoples have moved in time and space and have become culturally and religiously commingled in ways that modern demarcations of nationality fail to consider. The question of identity, whether cultural or political, takes into account the collective natural allegiance of the people to their nation.